High-accuracy experimental study of performance characteristics of optimised Ranque-Hilsch vortex tube - Chowdhury, NHK; Povey, T (Elsevier, 2024)
In this paper we present high-accuracy experimental measurements of the performance characteristics of an optimised Ranque-Hilsch vortex tube of cylindrical counter-flow design. Although this is a relatively mature research area, the published high-accuracy experimental data with quantified measurement uncertainty is very limited. The purpose is to provide a reference data-set for CFD method validation and calibration. The vortex tube design is a performance-optimum based on existing literature. We characterize the temperature separation, energy separation, efficiency, and coefficients of performance for three inlet pressures (3.0 bar, 5.0 bar and 7.0 bar) and for atmospheric back pressure. Performance characteristics are presented as a function of cold gas mass fraction. The lowest non-dimensional cold-exit temperature (normalised by inlet temperature) was 0.87, the highest coefficient of performance (decrease in enthalpy flux of the cold stream normalized by work needed to compress air to the inlet pressure) was 0.137, and the highest isentropic efficiency (ratio of the actual energy lost by cold stream to energy that would have been lost in an isentropic expansion of the entire inlet stream from the inlet pressure to the cold-exit pressure) was 0.16.